Strategy choices for casemix system at a private hospital in Indonesia - Nur Hidayah; Wanda Kiyah George Albert; Ekorini Listiowati; Husmiati Yusuf; Adi Fahrudin; Qurrotul ‘Aini (Universidad del Zulia, 2020)
Since January, first, 2014 Indonesia government has implemented National Health Insurance or Jaminan Kesehatan Nasional (JKN). The goal of The JKN is the Universal Health Coverage in Indonesia. In 2019, the member of JKN is 72% of the entire population of Indonesia. The change in the health service system to be opportunities or threats for hospitals as a part of the system. The tariff for health care service also has changed to INA-CBGs packages as a unique case-mix model for Indonesia. To capture the opportunities and face the threats, a private hospital need to apply appropriate strategies.